Speech-acts Strategies of Indonesian Television Talkshow Host: Indonesian Lawyer Club Weekly Program - Ani Rakhmawati; Intan Sulistyorini (English Department FBS UNP, 2021)
Becoming a successful television talk show presenter is an important effort to bring a program progressing smoothly to a successful ending. To accomplish this challenge, this article reports the result the analysis of one program namely the Indonesia Lawyers Club talk show hosted by Karni Ilyas. This paper aims to describe and explain: (1) the politeness strategies of the program host's, and (2) the expressive speech-act of the host in the Indonesia Lawyers Club talk show on television shows that air on TV One. The type of research is descriptive qualitative. Using purposive sampling, the data source was the episode of